Aspectos bioecológicos de parasitoides (Hymenoptera) da mosca-domediterrâneo (Diptera: Tephritidae) - Fernandes, Elania Clementino (Universidade Federal Rural do Semi-Árido, 2018)
The Mediterranean fruit fly Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) is one of the main fruit pests of economic and quarantine importance. Due to its great power of colonization and adaptation, this tefritídeo has been spreading throughout the tropical and subtropical region of the world, causing severe losses. The biological control of C. capitata with the use of parasitoids (Hymenoptera) is an important tool to reduce the populations of this tefritídeo. Among the main parasitoids of C. capitata we can report Aganaspis daci (Weld) (Hymenoptera: Figitidae), Pachycrepoideus vindemmiae Rondani (Hymenoptera: Pteromalidae), Spalangia cameroni Perkins (Hymenoptera: Pteromalidae) and Tetrastichus giffardianus Silvestre (Hymenoptera: Eulophidae). However, there are several factors that limit the choice or success of the use of parasitoids in biological control, among them we can highlight the lack of information on competition among the different groups of parasitoids, the lack of detailed information on rearing methodologies and the lack of studies on the bioecology of many species of parasitoids. Therefore, the objectives of this study were: 1) To evaluate the competition between the endoparasitoid of larva-pupa A. daci and the ectoparasitoids of pupa, P. vindemmiae and S. cameroni; 2) Adapt and describe in detail a rearing methodology for T. giffardianus; 3) To characterize the development and morphological aspects of the immature stages of T. giffardianus; 4) To evaluate the effect of different temperatures on the development of T. giffardianus and to elaborate its fertility life table. In the competition study between A. daci, P. vindemmiae and S. cameroni, a reduction in the emergence of A. daci was observed in the presence of the competitors; The sex ratio of offspring of A. daci was also significantly affected; But there was an additive effect on parasitism, especially between A. daci and P. vindemmiae. In the study of the rearing technique and the population growth potential of T. giffardianus, it was verified, through the demographic data of the studied population, that the rearing method presented in this study is feasible for the creation of T. giffardianus. The study of the development and morphological characterization of the immature stages of T. giffardianus demonstrated that the complete development (egg-adult) of this parasitoid takes place in 14 days and that through the form, coloration and size it is possible to characterize morphologically each of the immature stages of T. giffardianus. In the study on the effect of temperature on the biology and fertility life table of T. giffardianus, it was observed that temperature significantly influenced the development of the immature stages of this parasitoid, development occurred only at temperatures of 20, 25 and 30°C; The duration of pre-imaginal development (egg-adult) ranged from 41 days at 20°C to 11 days at 25°C; The mean longevity of males and females was inversely proportional to temperature, ranging from 50.3 to 8.4 days for males and from 31.8 to 8.0 days for females, in the thermal range of 15 to 35ºC. According to fertility life table data, the best performance of T. giffardianus occurred at 25°C
Título da TESE em língua estrangeira: Biologícal aspects of parasitoids (Hymenoptera) of the Mediterranean fly (Diptera: Tephritidae)
Keywords: Competição; Biologia; Insetos frugívoros; Semiarido; Competition; Biology; Biological control; Frugivorous insects; Semiarido; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA